2022
DOI: 10.1155/2022/3319646
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Metabolomics in Inflammatory Bowel Disease and Damp-Heat Syndrome: A Preliminary Study

Abstract: Aims. This study aims to investigate the potential biomarkers of inflammatory bowel disease (IBD) and IBD with damp-heat syndrome (IBD-DH) by metabolomics. Methods. Plasma and urine samples were collected from 15 healthy controls and 30 IBD patients, including 15 IBD-DH and 15 IBD with spleen deficiency syndrome (IBD-SD), which was coded as SF8G and SF70 according to the International Classification of Diseases Eleventh Revision (ICD-11) issued by World Health Organization. Pseudotargeted metabolomics method w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“… 31 Indolepropionic acid can catalyze the synthesis of indoleacetic acid. 32 Dietary indolepropionic acid supplementation attenuates atherosclerotic plaques. 33 These collectively highlight the potential of GMM-explained SMs (e.g., sebacic acid, EPA, and indoleacetic acid) in modulating cardiometabolic disease risk.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Indolepropionic acid can catalyze the synthesis of indoleacetic acid. 32 Dietary indolepropionic acid supplementation attenuates atherosclerotic plaques. 33 These collectively highlight the potential of GMM-explained SMs (e.g., sebacic acid, EPA, and indoleacetic acid) in modulating cardiometabolic disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were instances of variation between individual cases. For instance, one of the studies reported an increase in the level of phosphatidylcholine in CSF specimens [ 35 ], while some studies observed a decrease in the level of phosphatidylcholine in tears and plasma [ 37 , 90 ]. We observed similar findings for other metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the abundance of certain types of acylcarnitines can help to classify IBD, IBD with damp-heat syndrome (IBD-DH), and IBD with spleen deficiency syndrome (IBD-SD). Indeed, Wu et al demonstrated that three specific acylcarnitines (ACar 20:4, ACar 18:1, and ACar 20:3) were significantly increased in IBD plasma samples and that the ACar 8:1 was significantly increased in IBD with damp-heat syndrome when compared with IBD with spleen deficiency syndrome [141]. Another study found that the fecal acylcarnitine content in patients with IBD and mice with experimental colitis tended to increase compared to the control group, and the reason may be related to intestinal inflammation that led to mitochondrial dysfunction in the apical domain of the surface epithelium that may reduce the consumption of fatty acids [86].…”
Section: Relationships Of Octns With Altered Metabolite Profiles In I...mentioning
confidence: 99%